Blowout bifurcation of chaotic saddles - Tomasz Kapitaniak; Ying-Cheng Lai; Celso Grebogi (Discrete Dynamics in Nature and Society, 1999)
Chaotic saddles are nonattracting dynamical invariant sets that can lead to a variety of physical phenomena. We describe the blowout bifurcation of chaotic saddles located in the symmetric invariant manifold of coupled systems and discuss dynamical phenomena associated with this bifurcation.